Management of small bowel obstruction and therapeutic role of contrast media: A multicenter study - Liis Jaanimäe; Urmas Lepner; Ülle Kirsimägi; Ceith Nikkolo (Surgery in Practice and Science, 2023)
Background: Adhesive small bowel obstruction (SBO) accounts for 55–75% of mechanical small bowel obstructions [1,2]. According to guidelines, water-soluble contrast media (CM) is suggested in the diagnostic work-up of adhesive SBO [3–5]. However, there is currently no consensus on the therapeutic role of water-soluble CM in adhesive SBO [6] or a generally approved protocol as to when CM should be administered, how often should radiographs be taken and how long conservative management can safely be pursued. Material and methods: The data of patients who were hospitalized for SBO in two regional hospitals of Estonia between January 2015 and December 2019 were retrospectively collected from the hospitals’ electronic databases. Results: Of 1,008 patients with mechanical SBO included in analysis, 140 (13.9%) were operated on immediately. In the case of conservative management, 575 (66.2%) patients received CM. Resolution occurred in 75.8% of the patients who received CM and in 68.9% of the patients who did not (p = 0.037). Resolution rate was the highest (78.8%) in the group that received CM within 12 h of admission. The duration of symptoms was longer in patients who needed surgical intervention compared to conservatively treated patients (31 h vs 15 h, p<0.001). For patients with a history of a single previous abdominal/pelvic operation, the likelihood of surgical intervention was higher compared to patients whom resolution was achieved with conservative measures (50.9% vs 38.5%). In patients with three or more previous operations SBO resolved more often with conservative treatment compared to patients who required surgical intervention (22.7% vs 11.4%; p<0.001). Conclusion: The significantly higher rate of SBO resolution in the CM group suggests that CM may have a therapeutic role in SBO treatment, especially when it is administered within 12 h of admission. Patients with longer duration of symptoms and a history of one previous abdominal surgery need more likely surgical treatment.